PEMANFAATAN DIGITAL MARKETING UNTUK KOMUNIKASI BISNIS: Utilization of Digital Marketing for Business Communication - Pastima Simanjuntak; Koko Handoko; Hendri Kremer (ASOSIASI IDEBAHASA KEPRI, 2023)
Progress in the field of information transformation (communication) is accelerating, allowing information about specific situations to be transmitted independent of distance, space, or time. The advancement of information and communication technologies has rendered the flow of information unstoppable. Many new communication media, such as gadgets and smartphones, have emerged. With numerous communication tools and quick access to information, entrepreneurs may communicate with clients or other parties involved in their firm more easily. Hang Nadim Batam Riau Archipelago Vocational School provided the service.